The degeneration and replacement of dopamine cells in Parkinson’s disease: the role of aging - Rodriguez, Manuel; Morales, Ingrid; Rodriguez-Sabate, Clara; Sanchez, Alberto; Castro, Rafael; Brito, Jose Miguel; Sabate, Magdalena (Frontiers in Neuroanatomy, 2014)
Available data show marked similarities for the degeneration of dopamine cells in Parkinson’s disease and aging. The etio-pathogenic agents involved are very similar in both cases, and include free radicals, different mitochondrial disturbances, alterations of the mitophagy and the ubiquitin-proteasome system. Proteins involved in Parkinson’s disease such as α-synuclein, UCH-L1, PINK1 or DJ-1, are also involved in aging. The anomalous behavior of astrocytes, microglia and stem cells of the subventricular zone also changes similarly in aging brains and Parkinson’s disease. Present data suggest that Parkinson’s disease could be the expression of aging on a cell population with high vulnerability to aging. The future knowledge of mechanisms involved in aging could be critical for both understanding the etiology of Parkinson’s disease and developing etiologic treatments to prevent the onset of this neurodegenerative illness and to control its progression.